2004
DOI: 10.1111/j.1741-3737.2004.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Networks and Loneliness Among Elderly Jews in Russia and Ukraine

Abstract: The collapse of the Soviet Union had devastating consequences for the lives of its population, especially for older adults, many of whom became impoverished and were left with no social support. Using data from a survey of 2,579 elderly Jews in two of the largest countries of the former Soviet Union, Russia and Ukraine, we examine variables that affect their feeling of loneliness. Unmarried and childless elderly persons reported the highest feelings of loneliness. Married elderly persons who maintained frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 47 publications
(53 reference statements)
1
41
0
Order By: Relevance
“…14 The importance of friends has also been highlighted in other studies. 42, 51 Victor et al 25 found that education and age, but particularly the latter, also played a protective role; however these findings have generally not been supported in other research. 14,17 Having a pet (eg, dog, cat) has been suggested as protective of loneliness among older people, however empirical evidence is limited and findings equivocal.…”
Section: Community Settingsmentioning
confidence: 72%
“…14 The importance of friends has also been highlighted in other studies. 42, 51 Victor et al 25 found that education and age, but particularly the latter, also played a protective role; however these findings have generally not been supported in other research. 14,17 Having a pet (eg, dog, cat) has been suggested as protective of loneliness among older people, however empirical evidence is limited and findings equivocal.…”
Section: Community Settingsmentioning
confidence: 72%
“…It appears that in countries with generous social security schemes, where per capita public expenditure on health and welfare services is among the highest in Europe, people enjoy better social and psychological well-being than in countries where the state provides less. In many of the former socialist countries, formal support structures are largely absent (Iecovich et al 2004). Hence, older people in Eastern Europe may be particularly prone to loneliness because of inequalities in health, social integration, and socioeconomic resources, which in turn may be driven by macro-level socioeconomic inequalities and different levels of welfare provision.…”
Section: Discussionmentioning
confidence: 98%
“…In this paper, relying on the life course framework (Bengtson, Elder, & Putney, 2005;Elder, 1977Elder, , 1983Elder, Johnson, & Crosnoe, 2003) and the task-specific model of care provision (Iecovich et al, 2004), using qualitative methods we examine the preferences older individuals have from whom they would prefer to receive support in five different domains: meal preparation, personal care, transportation, financial support and personal support. The setting is a rural district in Northeast Thailand.…”
Section: Introductionmentioning
confidence: 99%